2016
DOI: 10.1371/journal.ppat.1005487
|View full text |Cite|
|
Sign up to set email alerts
|

The Myeloid LSECtin Is a DAP12-Coupled Receptor That Is Crucial for Inflammatory Response Induced by Ebola Virus Glycoprotein

Abstract: Fatal Ebola virus infection is characterized by a systemic inflammatory response similar to septic shock. Ebola glycoprotein (GP) is involved in this process through activating dendritic cells (DCs) and macrophages. However, the mechanism is unclear. Here, we showed that LSECtin (also known as CLEC4G) plays an important role in GP-mediated inflammatory responses in human DCs. Anti-LSECtin mAb engagement induced TNF-α and IL-6 production in DCs, whereas silencing of LSECtin abrogated this effect. Intriguingly, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
31
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(32 citation statements)
references
References 46 publications
(54 reference statements)
1
31
0
Order By: Relevance
“…EBOV GP-mediated cytokine induction in monocyte-derived dendritic cells is triggered not only by TLR4 but also by C-type lectin domain family 4 member G (CLEC4G/ LSECtin) (34). Expression of LSECtin on MDMs depends on IL-4 stimulation (54), and unstimulated MDMs, as used in the presented study, do not express LSECtin (54).…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…EBOV GP-mediated cytokine induction in monocyte-derived dendritic cells is triggered not only by TLR4 but also by C-type lectin domain family 4 member G (CLEC4G/ LSECtin) (34). Expression of LSECtin on MDMs depends on IL-4 stimulation (54), and unstimulated MDMs, as used in the presented study, do not express LSECtin (54).…”
Section: Discussionmentioning
confidence: 95%
“…It has been reported that this activation is triggered by the interaction of the EBOV glycoprotein (GP) with Toll-like receptor 4 (TLR4) (6,(27)(28)(29)(30)(31)(32)(33). In addition, GP has been shown to interact with C-type lectin domain family 4 member G (CLEC4G/LSECtin) on monocyte-derived dendritic cells, leading to the induction of an inflammatory response (34). A hallmark of severe EBOV disease and a predictor of fatal outcome is the induction of a strong inflammatory response as shown by elevated levels of inflammatory cytokines and chemokines (2-6, 8, 35).…”
mentioning
confidence: 99%
“…-28,63,69 A recent longitudinal study in a patient with severe EVD demonstrated that virus load in PBMCs correlates well with serum RNA levels,69 suggesting that virus replication in PBMCs contributes significantly to overall virus load. Consistent with the possibility that circulating monocytes support EBOV infection, Versteeg et al showed that at later times during experimental infection bone marrow derived monocytes 22,25,72,75,80,87,[95][96][97][98]. However, a recently appreciated caveat to these studies is the observation that bone marrow monocytes matured in vitro produce a heterogeneous population of cells, with cultures containing both DCs and M s 99.…”
mentioning
confidence: 90%
“…As a number of different cell types in addition to macrophages and DCs express TLR4, many additional host cells may contribute to the TLR4‐elicited cytokine storm that EBOV causes. Finally, in addition to TLR4, other currently unexplored EBOV/macrophage receptor interactions and subsequent signaling events may contribute to the production of the proinflammatory cytokines …”
Section: Ebov Elicits Mϕ Immunopathologymentioning
confidence: 99%
See 1 more Smart Citation